Implementasi Pendaftaran Tanah Sistematis Lengkap (PTSL) Sebagai Upaya Percepatan Pendaftaran Tanah Di Kota Bekasi - Ferdi Budiarsa; Maulana Rifai; Indra Aditya (Peneliti.net, 2022)
This study aims to examine and analyze the implementation of Complete Systematic Land Registration (PTSL) as an effort to accelerate land registration in Bekasi City. The theory used as a tool for analysis is the implementation theory of Van Meter and Van Horn. The method used is descriptive qualitative with data collection techniques carried out through observation, interviews and documentation then the data is analyzed with three stages namely reduction, presentation and drawing conclusions. The results of the research and discussion show that from 2018 to 2022 BPN Bekasi City has a target of 107,000 PTSL. The BPN invites the participation of sub-district administrators in collaboration with the implementation team for accelerating PTSL registration. The skills or attitudes of BPN Bekasi City employees are somewhat lacking in discipline due to late attendance, but communication between employees is built quite well because it is based on the principle of kinship. The emergence of illegal extortion activities (pungli) carried out by irresponsible individuals in the PTSL program in Bekasi City